In memoriam of Professor Hubert Wanyura - Różyło-Kalinowska, Ingrid; Stopa, Zygmunt (Journal of Stomatology, 2022)
Professor Hubert Wanyura, acknowledged Polish maxillofacial surgeon and researcher, passed away on January 14th, 2022 at the age of 80. One of his many achievements was the position of the Editor-in-Chief of the “Journal of Stomatology” (1995-2010), at that time published under the Polish title “Czasopismo Stomatologiczne”, which is the oldest Polish dental journal published since 1948, and the official organ of the Polish Dental Association.